2011
DOI: 10.1055/s-0030-1269886
|View full text |Cite
|
Sign up to set email alerts
|

Maternal-Fetal Outcome, Lipid Profile and Oxidative Stress of Diabetic Rats Neonatally Exposed to Streptozotocin

Abstract: This study showed that the experimental model used led to mild hyperglycemia during pregnancy, although it did not lead to increased macrosomic fetus rates. The hyperglycemic maternal environment caused metabolic alterations, including increased triglyceride and total cholesterol concentrations, and elevated oxidative stress, contributing to increase fetal visceral anomalies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 27 publications
0
28
1
1
Order By: Relevance
“…Nevertheless, a number of studies carried out in our laboratory found increased rates of pre-and postimplantation embryo losses and embryonic death (resorption), reduced number of live fetuses, and maternal weight gain during diabetic pregnancy. These alterations are due to metabolic changes caused by hyperglycemic peaks during pregnancy (Kiss et al 2009;Damasceno et al 2011;Iessi et al 2010;Saito et al 2010;Dallaqua et al 2012;Sinzato et al 2012). The divergent results shown in our study, which does not reinforce an effect of diabetes on the reproductive performance of rats, is possibly explained by mating time.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Nevertheless, a number of studies carried out in our laboratory found increased rates of pre-and postimplantation embryo losses and embryonic death (resorption), reduced number of live fetuses, and maternal weight gain during diabetic pregnancy. These alterations are due to metabolic changes caused by hyperglycemic peaks during pregnancy (Kiss et al 2009;Damasceno et al 2011;Iessi et al 2010;Saito et al 2010;Dallaqua et al 2012;Sinzato et al 2012). The divergent results shown in our study, which does not reinforce an effect of diabetes on the reproductive performance of rats, is possibly explained by mating time.…”
Section: Discussioncontrasting
confidence: 83%
“…The rates of preimplantation embryo loss were calculated by the formula: (number of corpora lutea− number of implantations)×100/number of corpora lutea. The rates of postimplantation loss were calculated by the formula: (number of implantations−number of live fetuses×100)/number of implantations (Damasceno et al 2008). When embryo or fetal development could not be observed, the uterus was stained by the Salewski's technique (Salewski 1964) for marking possible implantation points.…”
Section: Pregnancymentioning
confidence: 99%
“…The umbilical cord was clamped by using Halsteadtype hemostatic clamps. The rate of embryonic loss before and after implantation was calculated 24 . If there was a lack of visible implantation sites, the uterine corns were stained with a preparation of 10% ammonium sulfate 25 .…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, hydroureter may or may not be associated with congenital hydronephrosis, it might possibly be a transitory variation in rodents (Taylor 1986). According to the literature, approximately 20% of newborns of normal rats have this kind of visceral anomaly (Damasceno et al 2002b(Damasceno et al , 2011a.…”
Section: Citrus Aurantium Effects In Pregnant Ratsmentioning
confidence: 99%